Korelasi Asupan Zat Besi dan Protein dengan Kadar Ferritin Serum Ibu Hamil di Kabupaten Waled dan Sukabumi - Gumilang, Lani; Judistiani, Tina Dewi; Nirmala, Sefita Aryuti; Wibowo, Ari (Jurusan Ilmu Kesehatan Masyarakat, Fakultas Ilmu Keolahragaan, Universitas Negeri Semarang, Indonesia, 2021)
erritin is a measure of iron deficiency. Ferritin is a protein that is important in iron metabolism. Under normal conditions, ferritin stores iron which can be recovered for use as necessity. A cross-sectional study with correlational analysis design was carried out as part of the cohort study of pregnant women with the title Role of Vitamin D in Reducing Maternal and Infant Mortality in West Java. The number of samples was adjusted to the allocation of available funds, and successfully recruited as many as 150 pregnant women consecutively from the working area of Al Mulk and Waled General Hospital. The relationship between iron intake and serum ferritin levels was obtained p = 0.009, OR = 5,181; IK = - (2,881-0,410). The relationship between protein intake and serum ferritin content was obtained p = 0,041, OR = 0,142; IK = (0,084-3,823). There is a significant relationship between protein intake and iron intake with serum ferritin levels. Low intake of protein and iron significantly related to low serum ferritin levels as a risk factor. Keywords: Iron, Protein, Ferritin Serum, Pregnant Woman